Pseudo-linkage or real-linkage of rust resistance genes in a wheat-Thinopyrum intermedium translocation line - Jianbo Li; Merrill Ryan; Chongmei Dong; Kerrie L. Forrest; Matthew J. Hayden; Smriti Singh; Yuqi Wang; Nizam Ahmed; Robert A. McIntosh; Peng Zhang (Theoretical and Applied Genetics, 2025)

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Relationships of frequencies of extreme low temperatures with grain yield of some Australian commercial chickpea cultivars - Yashvir S. Chauhan; Sam Allard; Steve Krosch; Merrill Ryan; R. C. N. Rachaputi (International Journal of Biometeorology, 2022)
In this study, we examined the relationships between extremes of low temperatures and chickpea yield in 12 field experiments conducted at six sites in the subtropical environment of southeast Queensland (SEQ) from 2014 to 2019. Three commercial chickpea cultivars, PBA-Boundary, PBA-HatTrick and PBA-Seamer, were grown in all the experiments. Cultivars PBA-Pistol, PBA-Monarch and Kyabra were also included in three of these experiments conducted in 2015. In these experiments, the crop experienced a total of 8 to 41 frosts (minimum temperature < = 0 °C), 2 to 41 pre-flowering frosts, 2 to 19 frosts during the critical period, 0 to 13 frosts and 2 to 71 low-temperature days (< = 15 °C) after flowering. The mean yield, which varied from 1 to 3 t/ha, was negatively related to post-flowering frosts ( r = − 0.74, p < 0.01) and low-temperature days ( r = − 0.76, p < 0.01), and positively related to pre-flowering frosts ( r = 0.67, p < 0.05). Each post-flowering frost was associated with a 5% decrease and a low-temperature day with a 1% decrease in yield. The cultivar × site interaction was significant only in the three experiments with six commercial cultivars. This interaction was most likely due to an increase in the sensitivity range with additional cultivars, as indicated by frost damage scores and their relationships with yield. The results imply that extreme low-temperature events after flowering could negatively impact chickpea yield in SEQ and similar subtropical environments. Overcoming these effects through management and breeding should increase and stabilise chickpea yield.

Rates of parasitism, but not allocation of egg resources, vary among and within hosts of a generalist avian brood parasite - Loren Merrill; Scott J. Chiavacci; Ryan T. Paitz; Thomas J. Benson (Oecologia, 2017)

Dietary fat-dependent transcriptional architecture and copy number alterations associated with modifiers of mammary cancer metastasis - Ryan R. Gordon; Michele La Merrill; Kent W. Hunter; Peter Sørensen; David W. Threadgill; Daniel Pomp (Clinical & Experimental Metastasis, 2010)

Dietary fat alters pulmonary metastasis of mammary cancers through cancer autonomous and non-autonomous changes in gene expression - Michele La Merrill; Ryan R. Gordon; Kent W. Hunter; David W. Threadgill; Daniel Pomp (Clinical & Experimental Metastasis, 2010)

Genotype × diet interactions in mice predisposed to mammary cancer: II. Tumors and metastasis - Ryan R. Gordon; Kent W. Hunter; Michele La Merrill; Peter Sørensen; David W. Threadgill; Daniel Pomp (Mammalian Genome, 2008)